2014
DOI: 10.1016/j.bbmt.2014.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Liver-Type Fatty Acid-Binding Protein Linked with Increased Risk of Acute Kidney Injury after Allogeneic Stem Cell Transplantation

Abstract: Stem cell transplantation (SCT) involves a great risk of acute kidney injury (AKI). Urinary liver-type fatty acid-binding protein (uL-FABP) is a sensitive biomarker to detect kidney damage before an increase in serum creatinine (Cr); however, the utility of uL-FABP is not fully understood in the platform of SCT. A prospective study was conducted in 84 allogeneic SCT recipients to ascertain a link between the uL-FABP level before preparative procedures and AKI incidence after SCT. The association between them w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 33 publications
0
17
0
2
Order By: Relevance
“…This study suggests that more precise and suitable investigations are warranted to detect hidden mild kidney injury at baseline, for instance, using sensitive new urinary biomarkers. 30 AKI following SCT is reported to be a risk factor for CKD. 8,31 The Gray's analysis showed an association of early AKI with the incidence of CKD in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This study suggests that more precise and suitable investigations are warranted to detect hidden mild kidney injury at baseline, for instance, using sensitive new urinary biomarkers. 30 AKI following SCT is reported to be a risk factor for CKD. 8,31 The Gray's analysis showed an association of early AKI with the incidence of CKD in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary L-FABP can predict the onset of AKI after cardiac surgery [13,49,50], pediatric cardiopulmonary bypass [17], stem cell transplantation [12], and endovascular and open-abdominal aortic aneurysm repair [16] as well as in intensive care unit populations [15]. Additionally, L-FABP can also predict the progression to end-stage renal disease (ESRD), the onset of cardiovascular disease (CVD), or death for patients with AKI [14,51], type 2 diabetes [8,52], or chronic kidney a b Fig.…”
Section: Predicting Poor Outcomesmentioning
confidence: 99%
“…L-FABP has been shown to be a useful urinary biomarker for the diagnosis of renal disease in the following clinical conditions: diabetic nephropathy [6][7][8][9], anemia [10], acute kidney injury (AKI) [11][12][13][14][15][16], pediatric AKI [17], contrast medium-induced nephropathy [18,19], IgA nephropathy [20], human immunodeficiency virus (HIV)-associated nephropathy [21,22], and reduced graft function in renal transplantation [23,24]. Numerous AKI cohort studies have reported increased urinary levels of L-FABP in patients with septic shockinduced AKI [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…21 Furthermore, a recent prospective cohort study showed an increased risk of AKI following allogeneic HCT associated with an increase in urinary liver-type fatty acid-binding protein preceding preconditioning therapy. 22 Nevertheless, the clinical applicability of single biomarkers is still lacking solid evidence.…”
Section: Definition and Diagnosismentioning
confidence: 99%